2014
DOI: 10.1016/j.celrep.2014.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Transcriptional State to Large-Scale Repeat Expansions in Yeast

Abstract: SUMMARY Expansions of simple DNA repeats cause numerous hereditary disorders in humans. Replication, repair and transcription are implicated in the expansion process, but their relative contributions are yet to be distinguished. To separate the role of replication and transcription in the expansion of Friedreich’s ataxia (GAA)n repeats, we designed two yeast genetic systems that utilize a galactose-inducible GAL1 promoter, but contain these repeats in either the transcribed or non-transcribed region of a selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…Further investigation revealed that induction of transcription resulted in lower nucleosome occupancy in the upstream region containing the GAA tract. The authors conclude that transcriptional state, rather than transcription elongation through the repeat, was responsible for the 10-fold increase in expansion rate that occurred under induced conditions (Shah et al ., 2014). They speculate that the lower nucleosome occupancy occurring due to transcriptional activation allows more template switching during replication.…”
Section: Repeat Expansions Cause Human Diseasementioning
confidence: 99%
“…Further investigation revealed that induction of transcription resulted in lower nucleosome occupancy in the upstream region containing the GAA tract. The authors conclude that transcriptional state, rather than transcription elongation through the repeat, was responsible for the 10-fold increase in expansion rate that occurred under induced conditions (Shah et al ., 2014). They speculate that the lower nucleosome occupancy occurring due to transcriptional activation allows more template switching during replication.…”
Section: Repeat Expansions Cause Human Diseasementioning
confidence: 99%
“…In the short run, genetic and biochemical studies are needed to understand the role of Rad26p in TCR-mediated RIM, Pol32p subunit of DNA Polδ and DNA-helicase Pif1p in BIR mediated RIM as well as recombination proteins Rad51p and Rad52p in SSA-mediated RIM. Experimental systems designed to study repeat instability in a controlled transcription environment could be used to distinguish the relative contributions of transcription and replication in RIM [102]. One common and important feature of the replication-dependent and replication-independent pathways leading to RIM is the presence of single-stranded DNA (ssDNA) at the DSB site.…”
Section: Future Directionsmentioning
confidence: 99%
“…In the protocol below, we describe the use of our experimental system to select for large-scale expansions of H-DNA-forming (GAA) n repeats in S. cerevisiae [8, 10]. The yeast carry a selectable cassette consisting of a modified URA3 gene, which is counter-selectable on media containing the drug 5-fluoroorotic acid (5-FOA) [ see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the starting repeat length can be increased or decreased [8], or the (GAA)n repeats can be swapped out for other sequences such as SCA10 pentanucleotide (ATTCT)n repeats, or telomeric repeats [11, 12]. The URA3 promoter can be swapped for an inducible GAL1 promoter to study the effects of transcription [10]. The entire cassette can be moved to different locations, such as the non-essential arm of chromosome V, allowing for recovery of arm-loss events (double strand breaks that were not repaired) [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation